Attitude of common interest group members towards National Agricultural Technology Programme (Phase-I) interventions (Journal of the Bangladesh Agricultural University, 2020)
The main purpose of the study was to determine Common Interest Group members’ attitude towards National Agricultural Technology Programme (NATP) (phase-I) interventions in the selected areas of Mymensingh district and to explore the relationships between eleven selected characteristics of the CIG members and their attitude towards NATP (phase-I) interventions. A total of 110 CIG members were selected from CIG groups reside in Bailor and Rampur unions of Trishal upazila following simple random sampling technique. Data were collected during 23 September to 20 October, 2018 using a structured interview schedule through face-to-face interview method by the principal author himself. Data were analyzed with a combination of descriptive statistics and inferential statistical technique. Eleven selected characteristics of the CIG members namely; age, education, household size, farm size, annual income, farming experience, organizational participation, training received, credit received, agricultural subsidy received and extension media contact were considered to show relationships with their attitude towards NATP (phase-I) interventions. The majority (60%) of the CIG members had highly favourable attitude towards NATP (phase-I) interventions compared to 39.09% of the respondents had moderately favourable attitude and only 0.91% of the respondents had slightly favourable attitude towards NATP (phase-I) interventions. Correlation analyses indicated that the farm size, annual income, agricultural subsidy received and extension media contact had significant positive relationships with respondents attitude towards NATP (phase-I) interventions. So, these four characteristics had significant contributions on the attitude of CIG members. Age, education, household size, farming experience, organizational participation, training received and credit received had no significant relationship with respondents attitude towards NATP (phase-I) interventions. So, these characteristics had no significant contributions on the attitude of CIG members. The CIG members were found with very much enthusiastic about NATP (phase-I) interventions that could help policy makers to continue their efforts on that issue.J Bangladesh Agril Univ 18(1): 194–202, 2020https://doi.org/10.5455/JBAU.94764